Plant Use by the Funnel Beaker Farmers in Poland. New Archaeobotanical Data From Pottery Sherds and Daub Imprints - Dominika Kofel; Kamil Adamczak (Acta Universitatis Lodziensis: Folia Archaeologica)
The article presents the results of archaeobotanical studies on plant macroremains preserved both in charred form and as imprints in pottery and daub. The materials were collected from Funnel Beaker culture sites in Kałdus, Sławęcinek, Kietrz, and Małe Czyste. In total, 218 daub fragments and 33 pottery sherds were analysed. Most of the assemblages contained at least one of the searched items, such as imprints and/ or charred macroremains. Hulled wheat (Triticum monococcum/dicoccon/spelta) chaff, including glumes, glume bases, spikelet forks, and culms and blades of indeterminate cereals and/or wild grasses (Cerealia/Poaceae indet.), were among the most commonly found imprints. Interestingly, some assemblages contained crushed bones and microscopic charred wood fragments, illustrating a husbandry strategy that utilised all accessible resources.